Willing and Understanding: Late Medieval Debates on the Will, the Intellect, and Practical Knowledge
1 online resource
Keywords: Willing and Understanding elucidates a variety of issues in and approaches to debating the will-intellect interplay in the late Middle Ages. Authored by prominent scholars in the field, the contributions offer different perspectives on the development of late medieval theories of the will. Charting a dense map of voluntarist and epistemological ideas—entrenched leitmotifs of late medieval philosophy, seminal insights sparking original trends, and ephemeral novelties—the volume is a testimony to the conceptual multidimensionality and ethical complexity of the past and present iterations of the debate on the will. Contributors are Pascale Bermon, Magdalena Bieniak, Michael W. Dunne, Riccardo Fedriga, Giacomo Fornasieri, Tobias Hoffmann, Severin V. Kitanov, Monika Michałowska, Riccardo Saccenti, Sonja Schierbaum, Michael Szlachta, Łukasz Tomanek, and Francesco Omar Zamboni.